ACHIEVING EQUITY IN THE WORKPLACE: WOMEN WORKERS' RIGHTS IN THE SMALL BUSINESSES - Andini, Andini; Wahyuni, Wahyuni; Nurinayah, Nurinayah (Tadayun: Jurnal Hukum Ekonomi Syariah, 2024)
This study aims to analyze the fulfillment of women's labor rights at S Boutique Palu, which has been operating since 2013 in the fashion industry, amidst challenges faced by female workers related to labor regulations. Using a qualitative approach and empirical legal method, data were collected through observation, structured interviews, and documentation. The results show that, although S Boutique Palu has met some of the material requirements in employment contracts, several worker rights have not been optimally fulfilled, including insufficient wages, unfair work hour arrangements, and incomplete employment contracts. The study concludes by emphasizing the need for improvements in fulfilling women's labor rights in alignment with principles of justice and equality, along with recommendations to foster a better and more sustainable working environment in the small and medium business sector. Abstrak Penelitian ini bertujuan untuk menganalisis pemenuhan hak-hak tenaga kerja perempuan di Butik S Palu, yang beroperasi sejak 2013 dalam industri fashion, di tengah tantangan yang dihadapi pekerja perempuan terkait regulasi ketenagakerjaan. Dengan menggunakan pendekatan kualitatif dan metode hukum empiris, data dikumpulkan melalui observasi, wawancara terstruktur, dan dokumentasi. Hasil penelitian menunjukkan bahwa meskipun Butik S Palu telah memenuhi beberapa syarat materiil dalam perjanjian kerja, masih terdapat sejumlah hak pekerja yang belum terpenuhi secara optimal, termasuk upah yang tidak sesuai, pengaturan jam kerja yang tidak adil, serta kontrak kerja. Kesimpulan dari penelitian ini menekankan perlunya perbaikan dalam pemenuhan hak-hak pekerja perempuan agar sesuai dengan prinsip keadilan dan kesetaraan, serta rekomendasi untuk menciptakan lingkungan kerja yang lebih baik dan berkelanjutan di sektor usaha kecil dan menengah